Incidence of homologous recombination deficiency among high grade serous ovarian carcinoma patients from a tertiary care center in India - Goswami, Uddiptya; Ray, Vedanta; Ananthakrishnan, Ramya; Jayaraman, Kumanan; Mohapatra, Subhadarsini; Thirumalairaj, Raja (International Journal of Research in Medical Sciences, 2024)
Background: Ovarian cancer (OC) is the 9th most prevalent cancer overall in India and the 3rd most common among women, following breast and cervical cancers. According to GLOBOCAN 2022, there were 47,333 new OC cases and 32,978 deaths. Epithelial ovarian cancer (EOC) represents 90% of OC cases, of which 70% are high-grade serous ovarian cancer (HGSOC). Unfortunately, most patients are diagnosed at advanced stages III-IV. Homologous recombination deficiency (HRD) is a phenotype that is characterized by the inability of a cell to repair DNA double-strand breaks using the HRR pathway, leading to genomic instability and further malignant transformation. The Cancer Genome Atlas (TCGA) has reported HR deficiency in nearly 50% of HGSOC cases. Methods: This retrospective observational study evaluated 62 HGSOC patients treated at Apollo Cancer Centre Chennai from January 2021 to January 2024. Clinical data were collected from medical records. Formalin-fixed, paraffin-embedded (FFPE) tissue samples were obtained from patients undergoing surgery or biopsy and tested for HRD status. The data was analyzed and represented. Results: In the study population of 62 patients, 15 patients (24%) had HR deficiency (HRD positive).8 (13%) patients had poor quality FFPE tissue. Out of the 15 HRD-positive patients, six patients were TBRCA1, and four patients were TBRCA2. Five patients had GSS of more than 42. Conclusions: There is a significant population of HR-deficient HGSOC, comparable with the published literature. Thus, it serves as a predictive biomarker in ovarian cancers with deficiencies in DNA repair mechanisms.